Teaching Neuroscience: A Primer for Psychotherapists - Cabaniss, Deborah L. (Frontiers in Behavioral Neuroscience, 2018)
From the beginning of their psychotherapy training, students need to think about how talking changes the brain, how development is encoded in the body, and how connecting neuroscience and psychotherapy can help us improve psychosocial interventions to optimally help patients. But teaching neuroscience doesn't come naturally to many psychotherapy educators—myself included. We were trained as clinicians, not as researchers, so for many of us, reading and searching the neuroscience literature is challenging. Over many years, and with the help of wonderful colleagues, I am learning to read neuroscience papers and to incorporate what I learn into my psychotherapy teaching. When I teach neuroscience in a psychotherapy course, I do it with great humility. I make it very clear to my students that I'm not a neuroscientist and that I'm not an expert in the field. Instead, I learn with my students, as together we try to understand the science and what it can tell us about the mind, development, and psychotherapy. I also make it very clear that I'm not presenting this material as if it proves something about psychotherapy. We don't know enough about the neuroscience of psychotherapy to do that. Rather, I'm trying to get my students as excited as I am about what neuroscience can teach us about psychotherapy. My hope is that it will stimulate them to think about connections between neuroscience and psychotherapy when they are talking to patients, thinking about formulation, conceptualizing experiments and choosing their careers. Over the years, I've found that using carefully chosen neuroscience papers that I can understand really helps me to get the neuroscience/psychotherapy conversation going in a classroom. To that end, I offer five papers that I use when I teach psychotherapy. They are all written by top researchers and published in the nation's premiere scientific journals. Each one provides interesting potential insights into a different aspect of psychotherapy.